Hubungan Antara Kerapatan Kerinyu Dengan Luas Proyeksi Tajuk Dan Kerapatan Jati - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
ABSTRACT Kerinyu (Eupatorium odoratunt L.) population in teak forests should be managed due to their important roles. Research about the ecology of the population needs to be carried out to support the management of the population. The goals of the research were to examine the relationship between the density of teak and kerinyu and the relationship between the total teak crown coverage and the kerinyu density. The research was carried out by establishing 12 plots at a size of 10 x 10 m each where density, crown length, and crown width of teak were recorded. In the middle of each plot, a smaller plot at a size of 5 x 5 m was established and kerinyu density was recorded. Teak crown coverage was estimated by assuming that the shape of the crown projection was circular. The relationship between kerinyu density, the teak density and its total teak crown coverage was analysed using linear regression model performed by MINITAB statistical program. The effect of teak density and its total crown coverage on kerinyu population was deleterious. The relationship between the density of teak and kerinyu and the relationship between the total teak crown coverage and kerinyu density showed to form exponential patterns and negative correlations. The teak plantation suppressed kerinyu population.